(6х*14)/7 - 14/2=3
12х-7=3
12х=10
х=10/12
х=5/6
Ответ:х=5/6
(-5,4+1,6)+(-3,7)-(-10,5)= -3,8-3,7+10,5=10,5-7,5=3
Ответ:3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
(6х*14)/7 - 14/2=3
12х-7=3
12х=10
х=10/12
х=5/6
Ответ:х=5/6
(-5,4+1,6)+(-3,7)-(-10,5)= -3,8-3,7+10,5=10,5-7,5=3
Ответ:3
6/7х - 1/2 = 3/14
6/7х = 3/14 + 1/2
6/7х = 3/14 + 7/14
6/7х = 10/14
х = 10/14 : 6/7
х = 10/14 * 7/6
х = 5/6
1) -5,4 + 1,6 = -3,8
2) -3,8 + (-3,7) = -3,8 - 3,7 = -7,5
3) -7,5 - (-10,5) = -7,5 + 10,5 = 3